PEMBANGUNAN KAWASAN PERBATASAN INDONESIA DENGAN NEGARA MALAYSIA DI WILAYAH KECAMATAN BADAU KABUPATEN KAPUAS HULU - AGUS MULYANA,SH.A.21211035, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACTThis thesis researching the problems Indonesia Border Area Development In Malaysia In Sub Region Badau Kapuas Hulu. From the results of research using normative legal research methods can be concluded: 1. Government Policy in the Kapuas Hulu Development Plan, based on the provisions of Law Number 25, 2004 on National Development Planning System, which produces RPJPD Years 2005-2025, RKPD 2011-2015 and Kapuas Hulu budgeting. Prior to the formation of BNPP, BPP and BPP Provincial District as the implementation of Law Number 43, 2008 on Regional State President Jo Regulation Number 12, 2010 on the National Border Management, Border Area Development Planning Kapuas Hulu become an integral part of RPJPD, RPJMD and RKPD Kapuas Hulu. However, after the formation of BNPP, BPP and BPP Province Kapuas Hulu, border area development planning Kapuas Hulu on Priority Area (Locations Priority) Badau, Puring Kencana, Putusibau North, South Putusibau, Embaloh Hulu, and Trunk Lupar, switch to BNPP. 2. The presence of the Minister of Home Affairs Regulation Number 2, 2011 on Guidelines Establishment of Regional Border Management Agency, which regulates the powers, duties and functions of the Border Management Agency (BPP) BPP provincial and regency/city in Article 6 and Article 7, essentially a government takeover of authority Provincial and Regency / City Government as provided for in Article 11 and Article 12 of Law Number 43, 2008, which led to legal and technical issues in the implementation of border area development Kapuas Hulu aspect of applying the principle of deconcentration, desentraliasai and tasks. 3. Locations Priority Badau is an area that has a superior resource potential for development of local economic activity and encourage regional economic units. Badau strategic position in the border country that has direct access to the East Malaysian state Srawak a driving factor (push factor) for the economic development in the District and surrounding Badau, towards the realization of the border as the front porch Homeland. Further recommended that the Minister of Home Affairs Number 2, 2011 on Guidelines Establishment of Regional Border Management Agency, which regulates the powers, duties and functions of the Border Management Agency (BPP) BPP provincial and district / city to take over the authority of the Provincial Government and District/ City as provided in Article 6 and Article 7 of Law Number 43, 2008, to do a judicial review to the Supreme Court because it is against Article 11 and Article 12 of Law Number 43, 2008 on territory or "Cancel For Law".Keywords: Border Area DevelopmentABSTRAKTesis ini membahas masalah Pembangunan Kawasan Perbatasan Indonesia Dengan Malaysia Di Wilayah Kecamatan Badau Kabupaten Kapuas Hulu. Dari hasil penelitian mengunakan metode penelitian hukum normatif diperoleh kesimpulan : 1. Kebijakan Pemerintah Kabupaten Kapuas Hulu Dalam Menyusun Rencana Pembangunan Kabupaten Kapuas Hulu, berbasis pada ketentuan Undang-Undang Nomor 25 Tahun 2004 tentang Sistem Perencanaan Pembangunan Nasional, yang menghasilkan RPJPD Tahun 2005-2025, RPJMD 2011-2015 dan RKPD, serta APBD Kabupaten Kapuas Hulu. Sebelum terbentuknya BNPP, BPP Provinsi dan BPP Kabupaten sebagai implementasi dari Undang-Undang Nomor 43 Tahun 2008 tentang Wilayah Negara Jo Peraturan Presiden Nomor 12 Tahun 2010 tentang Badan Nasional Pengelola Perbatasan, Perencanaan Pembangunan Kawasan Perbatasan Kabupaten Kapuas Hulu menjadi bagian integral dari RPJPD, RPJMD dan RKPD Kabupaten Kapuas Hulu. Namun setelah terbentuknya BNPP, BPP Provinsi dan BPP Kabupaten Kapuas Hulu, penyusunan perencanaan pembangunan kawasan perbatasan Kabupaten Kapuas Hulu pada Lokasi Prioritas (LOKPRI) Badau, Puring Kencana, Putusibau Utara, Putusibau Selatan, Embaloh Hulu, dan Batang Lupar, beralih kepada BNPP. 2. Adanya Peraturan Menteri Dalam Negeri Nomor 2 Tahun 2011 Tentang Pedoman Pembentukan Badan Pengelola Perbatasan Di Daerah, yang mengatur wewenang, tugas, dan fungsi Badan Pengelola Perbatasan (BPP) Provinsi dan BPP Kabupaten/Kota dalam Pasal 6 dan Pasal 7, hakikatnya merupakan pengambilalihan kewenangan Pemerintah Provinsi dan Pemerintah Kabupaten/Kota sebagaimana diatur dalam Pasal 11 dan Pasal 12 Undang-Undang Nomor 43 Tahun 2008, yang memunculkan permasalahan yuridis maupun teknis dalam pelaksanaan pembangunan kawasan perbatasan Kabupaten Kapuas Hulu dari aspek penerapan asas dekonsentrasi, desentraliasai dan tugas pembantuan. 3. Lokpri Badau merupakan kawasan yang memiliki sumber daya unggulan potensial untuk dikembangkan mendorong kegiatan ekonomi lokal dan mendorong kegiatan unit-unit ekonomi kawasan. Posisi strategis Badau di wilayah perbatasan negara yang memiliki akses langsung dengan negara bagian Srawak Malaysia Timur merupakan faktor pendorong (push factor) bagi perkembangan perekonomian di Kecamatan Badau dan sekitarnya, menuju terwujudnya kawasan perbatasan sebagai beranda depan NKRI. Selanjutnya direkomendasikan agar Peraturan Menteri Dalam Negeri Nomor 2 Tahun 2011 Tentang Pedoman Pembentukan Badan Pengelola Perbatasan Di Daerah, yang mengatur wewenang, tugas, dan fungsi Badan Pengelola Perbatasan (BPP) Provinsi dan BPP Kabupaten/Kota dengan mengambil alih kewenangan Pemerintah Provinsi dan Pemerintah Kabupaten/Kota sebagaimana diatur dalam Pasal 6 dan Pasal 7, Undang-Undang Nomor 43 Tahun 2008, dapat dilakukan yudisial review kepada Mahkamah Agung karena bertentangan Pasal 11 dan Pasal 12 Undang-Undang Nomor 43 Tahun 2008 Tentang Wilayah Negara atau Batal Demi Hukum.Kata Kunci : Pembangunan Kawasan Perbatasan.